Концепція інформаційного Web-ресурсу підтримки рішень у сфері прогнозування - Твердохліб, Іван (Видавництво Львівської політехніки, 2014)
It is considered a problem of a substantiation of decisions at the choice of methods of forecasting with use of dynamic files of the empirical information on accuracy of forecasts of social and economic processes. It is proved expediency of use of the specialized databases of ratings of accuracy of forecasts for improvement of quality of a prediction in economy. It is offered the concept of an information Web-resource as displays of the consolidated information of accuracy of forecasts. It is developed information model of use of a Web-resource.
Keywords: прогнозування; якість прогнозів; системи підтримки рішень; бази даних; Web-ресурс; консолідована інформація; інформаційна модель